Association Between Anti-Tuberculosis Drug Side Effects and Medication Adherence Among Pulmonary Tuberculosis Patients at Wijaya Kusumah Hospital, Kuningan, Indonesia - Vera Mulyawantie; Juju Jumiati; Fitri Indrayani (CV. Science Tech Group, 2026)
Tuberculosis (TB) remains one of the leading infectious diseases worldwide and continues to be a major public health concern in Indonesia. The success of anti-tuberculosis treatment depends largely on patients' adherence to medication. However, the occurrence of adverse drug reactions during treatment may reduce adherence and compromise treatment outcomes. This study aimed to determine the association between anti-tuberculosis drug side effects and medication adherence among pulmonary tuberculosis patients at Wijaya Kusumah Hospital, Kuningan. A quantitative observational study with a cross-sectional design was conducted among pulmonary tuberculosis patients receiving anti-tuberculosis treatment at Wijaya Kusumah Hospital, Kuningan. A total of 52 respondents were recruited using total sampling. ADRs were assessed using a structured questionnaire, while medication adherence was measured using the eight-item Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using the Chi-square test with a significance level of 0.05. Most respondents experienced severe ADRs (57.7%), while 63.5% demonstrated low medication adherence. Statistical analysis showed a significant association between ADRs and medication adherence (p = 0.040). Patients who experienced more severe ADRs were more likely to demonstrate poor adherence during treatment. ADRs were significantly associated with medication adherence among pulmonary tuberculosis patients. Early identification and appropriate management of adverse drug reactions are essential to improve medication adherence and enhance treatment success. Improving medication adherence and reducing treatment failure may contribute to decreasing the transmission of drug-resistant tuberculosis within communities, protecting vulnerable populations, supporting Sustainable Development Goal (SDG) 3 (Good Health and Well-being), and strengthening health systems in resource-limited settings such as Indonesia.